Race, gender and the body in British immigration control : subject to examination - Smith, Evan; Marmo, Marinella (Migration, Diasporas and Citizenship, 2014)
01 02 Race, Gender and the Body in British Immigration Cont ro l provides the most detailed account of the virginity testing controversy in the late 1970s, and demonstrates that this abusive practice, which was endured by South Asian women for more than a decade, was part of a wider culture of mistreatment and discrimination that occurred within the immigration system authorized by the state. Using recently opened government documents, Smith and Marmo offer a unique insight into this matter and uncover the extent to which these women were scrutinized, interrogated and subject to physical examination at the border. Combining cutting-edge criminological theory and historical research, this book proposes that the contemporary British immigration control system should be viewed as an attempt to replicate colonial hierarchies upon migrants in the post-imperial era. For this reason, the abuses of human rights at the border became a secondary issue to the need of the post-imperial British nation-state to enforce strict immigration controls. 04 02 Introduction 1. Decolonisation and the Creation of the British Immigration Control System 2. The Border as a Filter: Maintaining the Divide in the Post-Imperial Era 3. Reorienting the South Asian Female Body: the Practice of 'Virginity Testing' and the Treatment of Migrant Women 4. Deny, Normalise and Obfuscate: the Government Response to the Virginity Testing Practice and Other Physical Abuses 5. The Postcolonial World Stage: Immigration and Britain's International Reputation 6. Discrimination by other Means: Further Restrictions on Migrant Women and Children under the Conservatives Conclusion 02 02 This book analyses the practice of virginity testing endured by South Asian women who wished to enter Britain between the late 1960s and the early 1980s, and places this practice into a wider historical context. Using recently opened government documents the extent to which these women were interrogated and scrutinized at the border is uncovered. 08 02 "An important and revelatory study of a shameful episode in 20th century British immigration history that was shaped by Imperial racism." - Alan Travis, Home Affairs Editor, The Guardian "It is impossible to over-estimate the importance of Smith and Marmo's study. Their chilling documentation of abuses permitted – and vigorously denied – by the Home Office represents feminist scholarship at its best." - Philippa Levine, Mary Helen Thompson Centennial Professor in the Humanities, University of Texas at Austin, US "This historical study examines the intertwining of 'race', gender and the body in the application of immigration controls in Britain since the 1970s. Drawing on research in British Government archives, 'Race, Gender and the Body in British Immigration Control' begins with the shocking case of virginity testing of a 35 year old woman, who arrived at Heathrow Airport, London in 1979 to marry her fiancé. Smith and Marmo unpick these obscene practices as symptomatic of the de-humanising treatment of migrants from the former colonies and the dense racialized, sexual politics of British border controls. Crucially, Smith and Marmo also explore the incredible resistance of South Asian women and anti-deportation activists against the discriminatory practices of the British state. This important new history of immigration control speaks directly to the contemporary situation of border securitisation in Britain and beyond. It will be of interest to, and will be widely read by all interested in migration, citizenship, human rights, post-colonial migration, and histories of resistance to unjust border controls." - Dr Imogen Tyler, Senior Lecturer in Sociology, Lancaster University, UK 13 02 Evan Smith is Vice-Chancellor's Postdoctoral Research Fellow in the School of International Studies at Flinders University, Australia. He has written widely on the British immigration control system, the politics of race in Britain and the British far left. Marinella Marmo is Associate Professor in Criminology at Flinders University Law School, Australia. Her research interests include international criminal justice, transnational crime and comparative criminology.